Analisis Plagiarisme Skripsi Mahasiswa Bimbingan dan Konseling Tahun 2016-2017 Universitas Jambi - Meli Ismawati; Akmal Sutja; Fellicia Ayu Sekonda (Journal on Education, 2023)
In the world of education, plagiarism can be said to be part of academic work in an institution, one of which is done by many students accidentally or unintentionally. In general, in making theses, students often use the same references, one of the variables is the title of the thesis that has something in common, imitating research methods, and some students even just change the place and subject of research with the same topic. This research is limited to existing problems, while the limitations of the problem in this research are theses that have similar content, have similar references, have similar titles, and this research is only limited to the thesis of Guidance and Counseling students who have completed IS Studies at University 2016-2017 Jambi, the purpose of this research is to find out what types of plagiarism are in the thesis of Guidance and Counseling Students who have completed IS Studies in 2016-2017 University of Jambi. The type of research used was library research, the subject of this research was 20 undergraduate thesis students of the Guidance and Counseling Study Program, Faculty of Teaching and Education, Jambi University in 2016-2017 whose thesis had the same title, the data collection methods used by researchers included observation and documentation. Based on the results of research that has been conducted by researchers, checking 20 student thesis Guidance and Counseling Study Program Jambi University in 2016-2017 through the Turnitin application, it can be concluded that only 17 theses can be used as a reference, 6 theses have a moderate Similarity index and 11 theses have a Similarity index total and there is plagiarism in CHAPTER I, CHAPTER II, CHAPTER III, CHAPTER IV and CHAPTER V, based on 4 types of plagiarism namely idea plagiarism, content plagiarism, plagiarism of words, sentences, paragraphs and total plagiarism, dominant students plagiarism in the category of idea plagiarism and plagiarism of words, sentences, and paragraphs